2016
DOI: 10.1002/2016jc012221
|View full text |Cite
|
Sign up to set email alerts
|

On the generation and evolution of internal solitary waves in the southern Red Sea

Abstract: Satellite observations recently revealed trains of internal solitary waves (ISWs) in the off‐shelf region between 16.0°N and 16.5°N in the southern Red Sea. The generation mechanism of these waves is not entirely clear, though, as the observed generation sites are far away (50 km) from the shelf break and tidal currents are considered relatively weak in the Red Sea. Upon closer examination of the tide properties in the Red Sea and the unique geometry of the basin, it is argued that the steep bathymetry and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
(62 reference statements)
3
23
0
Order By: Relevance
“…In the southern Red Sea, two long areas with high KE values along the edges of slopes, with higher values at the western side, indicate that baroclinic tides are mostly generated near the slopes and propagate toward the center of the trench. This is consistent with previous studies of ISWs in the southern Red Sea based on satellite observations (Da Silva et al, ) and numerical models (Guo et al, ), which revealed that the ISWs are formed from internal tides generated at the slopes on both sides of the sea and propagated toward the center. In most parts of the central and northern Red Sea, the KE of baroclinic tides are below 0.1 kJ/m 2 , indicating very little baroclinic tide activity; in the north, there are intense signals exhibiting at the edge of the slope at the entrance of the Gulf of Suez and near the steep sea ridge at the Strait of Tiran.…”
Section: Basic Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…In the southern Red Sea, two long areas with high KE values along the edges of slopes, with higher values at the western side, indicate that baroclinic tides are mostly generated near the slopes and propagate toward the center of the trench. This is consistent with previous studies of ISWs in the southern Red Sea based on satellite observations (Da Silva et al, ) and numerical models (Guo et al, ), which revealed that the ISWs are formed from internal tides generated at the slopes on both sides of the sea and propagated toward the center. In most parts of the central and northern Red Sea, the KE of baroclinic tides are below 0.1 kJ/m 2 , indicating very little baroclinic tide activity; in the north, there are intense signals exhibiting at the edge of the slope at the entrance of the Gulf of Suez and near the steep sea ridge at the Strait of Tiran.…”
Section: Basic Characteristicssupporting
confidence: 93%
“…Da Silva et al () reported, based on satellite observations, that the southern Red Sea was a new hot spot for internal solitary waves (ISWs). Guo et al () further explored the generation processes of the ISWs using a 2‐D numerical model, revealing that the dominant mechanism is the nonlinear evolution of an internal tide. The tidal characteristics in the BAM Strait has been explored using in situ observations (Jarosz, Murray, & Inoue, ) and a 2‐D numerical model (Jaros, Blain, et al ), with main focus on the activities of barotropic tides.…”
Section: Introductionmentioning
confidence: 99%
“…warmer and fresher water by eddies reduces the intrinsic meridional gradient and flattens the isopycnals, which in turn limits the eddy generation and was interpreted as a typical negative feedback mechanism (Zhan et al 2019). Based on WRF-MITgcm-CMS simulations, the Red Sea mesoscale circulation was found to play an important role in transporting biogeochemical tracers within the basin (Fig.9) and in supporting the marine ecosystem (Zhan et al 2014;Dreano et al 2016;Raitsos et al 2017;Guo et al, 2020).…”
Section: Study Of the Red Sea Region Circulation Climate And Ecosystemmentioning
confidence: 99%
“…Guo et al 2016). Barotropic tides generate internal tides and solitary waves, mainly on the steep sides of the deep trough in the southern part of the Red Sea(da Silva et al 2012;Guo et al 2016).Our simulations using a 200 m non-hydrostatic MITgcm and CMS showed that the breaking of internal waves induces vertical mixing, which could increase the supply of nutrients to the euphotic zone and enhance biological productivity, by disrupting the pycnocline and inducing turbulence(Guo et al 2020).Waves: Based on long-term WWIII simulations forced with the in-house WRF downscaled Red Sea reanalysis, the wave variability in the Red Sea was naturally associated with the dominant regional wind regimes(Langodan et al 2014). Although wind intensity in the basin is usually moderate, a prolonged duration and the existence of a long fetch may give rise to waves that reach up to 3.5 m. The irregular shape of the Red Sea coast creates shadowed areas, especially in the south where southward-moving waves reduce to swell and propagate unidirectionally.…”
mentioning
confidence: 99%
“…Guo et al (2016) investigated and described the 2D ISW shoaling process in the southern Red Sea. This study improved on the 2D experiment of Guo et al (2016) by removing the background barotropic tidal velocities to examine the shoaling process. The 2D study presents a similar evolution process, despite the limitations of a 2D setup and the presence of GUO ET AL.…”
Section: Potential Temperature Field Along Wave Propagation Transectsmentioning
confidence: 99%